2021
DOI: 10.1186/s12889-021-11309-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in child abuse experience associated to sleep quality: results of the Korean Children & Youth Panel Survey

Abstract: Background A victim of child abuse can often develop mental illness. The early detection of mental illness of children could be supported by observing sleep quality. Therefore, we examined the relationship between sleep quality and the changes in child abuse by the child’s own parents over the study period. Methods Data from the 2011–2013 Korean Children and Youth Panel Survey was used, and 2012 was set as the baseline. Adolescents who had poor sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Adolescents experiencing physical abuse at home may attend school physically injured and/or depressed and tired due to sleeplessness resulting from child abuse (Chae et al, 2021; Hildenbrand et al, 2018; Sutter et al, 2023). One could argue from a state dependence perspective that appearing tired, weak, detached, and sad may boost the likelihood that adolescents will be victimized repeatedly given the ease with which they can be bullied, but not necessarily long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents experiencing physical abuse at home may attend school physically injured and/or depressed and tired due to sleeplessness resulting from child abuse (Chae et al, 2021; Hildenbrand et al, 2018; Sutter et al, 2023). One could argue from a state dependence perspective that appearing tired, weak, detached, and sad may boost the likelihood that adolescents will be victimized repeatedly given the ease with which they can be bullied, but not necessarily long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…Living with domestic violence may result in sleep deficiency that persists even after the abuse has ended [ 134 ]. Similarly, children who have experienced either physical and/or sexual abuse report more sleep deficiency issues than children who are not abused [ 135 , 136 ], and these effects on sleep are long-term [ 137 , 138 ]. Specifically, victims of abuse demonstrate prolonged sleep latency, decreased sleep efficiency, increased nighttime activity and wakefulness, and decreased sleep duration as measured by surveys [ 135 ] and polysomnography [ 139 , 140 ].…”
Section: Nutrition Dietary Intake and Weightmentioning
confidence: 99%
“…Sleep disturbances tend to increase during adolescence due to a combination of puberty‐related shift in circadian rhythm and psychosocial changes that result in restricted and irregular sleep (Crowley, Wolfson, Tarokh, & Carskadon, 2018). ELA has been associated cross‐sectionally with greater sleep disturbances during adolescence (April‐Sanders et al., 2021; Chae, Jang, Park, & Jang, 2021; Langevin et al., 2019; McPhie, Weiss, & Wekerle, 2014; Park et al., 2021; Turner et al., 2020; Wang, Raffeld, Slopen, Hale, & Dunn, 2016; Xiao et al., 2020). While few longitudinal studies have been conducted, one prospective, longitudinal study found that ELA is associated with greater sleep disturbances during adolescence, but not during childhood (April‐Sanders et al., 2021), suggesting that the normative increases in sleep disturbance during adolescence represent a double hit for individuals with a history of ELA (Fuligni, Chiang, & Tottenham, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a lack of longitudinal studies, previous studies examining the association between ELA and sleep during adolescence have mostly relied on self‐reported measures to assess ELA (April‐Sanders et al., 2021; Chae et al., 2021; McPhie et al., 2014; Park et al., 2021; Turner et al., 2020; Wang et al., 2016; Xiao et al., 2020) as well as utilized a cumulative risk approach where the number of adverse events is summed, regardless of the severity of the events (e.g., April‐Sanders et al., 2021; Wang et al., 2016). These methods may not fully capture the multifaceted and complex experience of ELA exposure.…”
Section: Introductionmentioning
confidence: 99%